Character Development of Students through Extracurricular Activities - Sereth Sosiden; Pisuth Viraek (Journal La Edusci, 2021)
The goal of this study is to figure out the benefits of having extracurricular activities in schools so that they become a factor when people think about going to college. The type of research is qualitative with an ex post facto model, and it's done that way. The method used to get data in this study is called field research, and it includes things like observations, interviews, and documentation. The total number of people in this study was 153, and the total number of people in the sample was 21. This study found that extracurricular activities can help students develop a variety of character traits, including: In (b) the flag ceremony, students learned how to be disciplined, patriotic, and able to defend their country. The role of nationalism and the country as a whole. (c) When individuals do exercise, they become disciplined, orderly, keep their bodies healthy, and build relationships with other people. (d) Scouting: Activities that build a democratic, confident, obedient to social rules, spirit of cooperation, respect for diversity, independence, discipline, hard work, and responsibility are all part of Scouting. While the things that help and hurt extracurricular activities are (a) the enthusiasm and enthusiasm of the students, the cohesiveness of all parties, parental support, the teacher's role model, good communication between students and teachers, and enough time. (b) things that make it hard to do something Lack of teachers for extracurricular activities, different family backgrounds, and limited facilities and infrastructure make it hard to do extracurricular activities.